A sample survey in school children regarding prevalence of deafness and its relationship with academic proficiency - Mukherjee AT; Rekha Roy (Journal of All India Institute of Speech and Hearing, 1970)
The object of this study was tofindout the incidence of children having hearing loss in the children studied at random from among the students between age group of 5 to 10 years studying in class I,II. III, IV, V and VI in some of the schools in Calcutta